(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Ultrasound, as an emerging green technology has received increasing attention of the petroleum industry. The diversity of ultrasound techniques used in oil and gas pipeline plants provides us with a wealth of information on how to exploit this technology when combined with other techniques, in order to improve the quality of analysis. The fundamental theory of ultrasonic nondestructive evaluation (NDE) technology is offered, along with practical limitations as related to two factors (wave types and transducers). This review paper presents applications and limitations of some ultrasonic techniques. The paper demonstrates the fundamental theory of ultrasound and type of waves used and examines the inspection approaches of the contact and angle beam techniques. This review also clarifies and discusses the options used in solving the industrial engineering problem, with a comprehensive historical summary of the information available in the literature. Merging various NDE inspection techniques into the testing of objects is discussed